2007
DOI: 10.1902/jop.2007.070149
|View full text |Cite
|
Sign up to set email alerts
|

GCF MMP‐8 Levels in Smokers and Non‐Smokers With Chronic Periodontitis Following Scaling and Root Planing Accompanied by Systemic Use of Flurbiprofen

Abstract: Flurbiprofen administration had no additional inhibitory effect over SRP alone on GCF levels of MMP-8 in smokers compared to non-smokers with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…Of these, five studies were excluded. After the final stage of selection, nine studies were included and processed for data extraction (ĸ score for inter‐assessor agreement at full‐text eligibility kappa = .90) . The study identification flowchart according to PRISMA is shown in Figure …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, five studies were excluded. After the final stage of selection, nine studies were included and processed for data extraction (ĸ score for inter‐assessor agreement at full‐text eligibility kappa = .90) . The study identification flowchart according to PRISMA is shown in Figure …”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were included for the present systematic review . All studies were prospective non‐RCT and were carried out in Turkey, the USA, and Japan .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research has demonstrated reduction in oxidative stress after non‐surgical periodontal therapy, no current studies definitively demonstrate an adjunctive benefit of antioxidant treatment 52 . Non‐steroidal anti‐inflammatory drug use as an adjunct to non‐surgical therapy in smokers has been shown to demonstrate clinical and biologic improvements in periodontal parameters and may represent an additional mechanism to improve outcomes of periodontal therapy in smokers 53–55 …”
Section: Discussionmentioning
confidence: 99%
“…4,5 Cigarette smoking affects neutrophil function which are major source of matrix metalloproteinase-8 (MMP-8). 6,7 Cigarette smoke contains a mixture of chemicals having carcinogenic potential, as well as various stable and free radicals species, and ROS that causes cellular oxidative stress, which is a factor for many smoking-related diseases. This smoke-induced oxidative stress has the potential to alter the MMP activity.…”
Section: Introductionmentioning
confidence: 99%